THE ROLE OF THE CONTINUOUS EDUCATION (UPBRINGING) CONCEPT IN THE SPIRITUAL DEVELOPMENT OF STUDENTS IN GENERAL SECONDARY EDUCATION - Obboskhonov , Alimardon; Boymurodov , Sanjar (Oriental Journal of Education, 2026)
This article analyzes the step-by-step implementation of the Continuous Spiritual Education Concept in shaping students’ spiritual and moral development in general secondary education.